The role of partnering and assortative mating for income inequality: The case of Finland, 1991–2014 - Erola Jani; Kilpi-Jakonen Elina (SAGE Publications Ltd, 2022)
Previous studies covering various developed countries suggest that changes in assortative mating by education have contributed only a little to the changes in income inequality, opposite to the expectations of many. In this paper we consider two potential reasons for the zero effects: (a) that it is the selection into partnership rather than assortative mating according to specific characteristics that matters; and (b) that for assortative mating to matter, a broader spectrum of matching characteristics than just education should be considered, such as matching by employment and social origin. We study these assumptions using register data on household income inequalities, education, employment and parental class background in Finland 1991–2014. We analyze men and women separately and focus on individuals aged 35–40. We concentrate on between-group income inequality as measured by the Theil index. The results suggest that partnership is an important factor behind income inequality, and changes in selection into partnership can explain a substantial part of the changes in income inequality. Assortative mating does not matter as much, even if more sorting characteristics are taken into account. Social origin contributes very little to the income inequality of families in Finland.
Dataset:10.5281/zenodo.5412563